Problems in Implementing Asr Congregational Prayer to Enhance the Worship Quality of Students - Jesi Tria Tria Paliban; Rita Yulia Anggraini (Departement of Mathematics Education, 2024)
Worship has the primary purpose of devotion to Allah and simplicity in intention towards Him, whether in times of joy or hardship, with the hope of attaining happiness in the Hereafter. One example is prayer. Additionally, worship aims to distance oneself from wrongdoing and evil deeds and can achieve other objectives through the performance of prayer. The aim of this research is to identify issues in the implementation of congregational Asr prayer in an effort to enhance the quality of Asr prayer worship and to find solutions to these issues at SMP Muhammadiyah Kota Pagar Alam. This study uses a qualitative method with a purposive sampling technique, and data collection is done through observation, interviews, and documentation. The results of the study indicate that the issues in the implementation of congregational Asr prayer in improving the quality of worship include various excuses, negligence in bringing prayer garments, inadequate facilities, lack of discipline in maintaining prayer, insufficient cooperation with parents, and lack of concentration in performing congregational prayer.